2016
DOI: 10.1111/nicc.12239
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, knowledge and practices concerning delirium: a survey among intensive care unit professionals

Abstract: Identification of implementation barriers for adherence to guidelines pertaining to delirium is feasible with a survey. Results of this study may help to design-targeted implementation strategies for ICU delirium management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 41 publications
6
78
1
11
Order By: Relevance
“…This unsatisfactory practice may results from their poor knowledge and their negative attitude toward delirium as well as may because lack of studied nurses' autonomy as they expected to obtain direction on patient care from physicians. This results contradicted with [21] who founded that The majority of the respondents were frequently performed promotion of day time wakefulness (81%), use of glasses when patients are visually impaired (74%) and use of hearing aids when patients are hearing impaired (67%). However, Yue et al, [20] explained unsatisfactory delirium practice from the side of nurses resulting from the lack of knowledge, absence of evidence-based nursing practice, complex symptoms, and changing shifts which leads to difficulties in detecting the early delirium signs.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…This unsatisfactory practice may results from their poor knowledge and their negative attitude toward delirium as well as may because lack of studied nurses' autonomy as they expected to obtain direction on patient care from physicians. This results contradicted with [21] who founded that The majority of the respondents were frequently performed promotion of day time wakefulness (81%), use of glasses when patients are visually impaired (74%) and use of hearing aids when patients are hearing impaired (67%). However, Yue et al, [20] explained unsatisfactory delirium practice from the side of nurses resulting from the lack of knowledge, absence of evidence-based nursing practice, complex symptoms, and changing shifts which leads to difficulties in detecting the early delirium signs.…”
Section: Discussioncontrasting
confidence: 54%
“…Also, Yue, et al, [20] who stated lack of knowledge and skills required to assess and manage the delirium patients lead to preventing nurses from recognizing early symptoms. As well as Trogrlic et al, [21] who made a survey among intensive care unit professionals about their attitude, knowledge and practices concerning delirium, the study indicated that knowledge deficit were presented more clearly in nurses than in physicians. Another supported study made by Flaigle et al, [22] who make a study on 105 nurse and found that nurses who answered each question correctly ranged from 35% to 100% and only one nurse scored 100% , the staff required further education regarding the importance, risk factors, and treatments for pediatric delirium.…”
Section: Discussionmentioning
confidence: 98%
“…It is likely that the lack of incentives to complete the survey and lack of time due to the nature of work in the ICU setting might be contributory. Previous surveys in Europe among ICU nurses have similarly reported low response rates (Fulbrook, Albarran, Baktoft, & Sidebottom, 2012;Trogrlić et al, 2017). Finally, the survey asks the respondents to rate themselves so there can be a certain level of self-perception bias incorporated into the results.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Missing knowledge and training were identified as major factors in the implementation of delirium management (Elliott, 2014). Trogrlić et al (2016) added missing co-operation between physicians and nurses as a barrier, and Richardson et al (2016) pointed out that the differentiation between delirium and dementia is not well established yet. Inter-professional training and education is not well established, leading to the usage of different assessment tools within different professions (Bellelli et al, 2014).…”
Section: Barriersmentioning
confidence: 99%
“…Previous surveys from recent years were considered to design a new and adapted survey (Morandi et al, 2013;Luetz et al, 2014;Demir Korkmaz et al, 2016;Saller et al, 2016;Selim and Wesley Ely, 2017;Trogrlić et al, 2016). The main result of all surveys mentioned above was a lack of adherence to existing guidelines, a large variation of assessment methods and a lack of knowledge of health care providers.…”
Section: Introductionmentioning
confidence: 99%